Technical failure during colorectal endoscopic full-thickness resection: the “through thick and thin” study - Gibiino, Giulia; Binda, Cecilia; Papparella, Luigi Giovanni; Spada, Cristiano; Andrisani, Gianluca; Di Matteo, Francesco Maria; Gagliardi, Mario; Maurano, Attilio; Sferrazza, Sandro; Azzolini, Francesco; Grande, Giuseppe; de Nucci, Germana; Cesaro, Paola; Aragona, Giovanni; Cennamo, Vincenzo; Fusaroli, Pietro; Staiano, Teresa; Soriani, Paola; Campanale, Mariachiara; Di Mitri, Roberto; Pugliese, Francesco; Anderloni, Andrea; Cucchetti, Alessandro; Repici, Alessandro; Fabbri, Carlo; The “through thick and thin” study group; Sbrancia, Monica; Coluccio, Chiara; Frazzoni, Leonardo; Barbaro, Federico; Petruzziello, Lucio; Vieceli, Filippo; Mandarino, Francesco Vito; Cocca, Silvia; Ghersi, Stefania; Manno, Mauro; Amata, Michele; Dioscoridi, Lorenzo; Mutignani, Massimiliano (Endoscopy, 2024)
Background Endoscopic full-thickness resection (EFTR) is an effective and safe technique for nonlifting colorectal lesions. Technical issues or failures with the full-thickness resection device (FTRD) system are reported, but there are no detailed data. The aim of our study was to quantify and classify FTRD technical failures.Methods We performed a retrospective study involving 17 Italian centers with experience in advanced resection techniques and the required devices. Each center shared and classified all prospectively collected consecutive failures during colorectal EFTR using the FTRD from 2018 to 2022. The primary outcome was the technical failure rate and their classification; secondary outcomes included subsequent management, clinical success, and complications.Results Included lesions were mainly recurrent (52 %), with a mean (SD) dimension of 18.4 (7.5) mm. Among 750 EFTRs, failures occurred in 77 patients (35 women; mean [SD] age 69.4 [8.9] years). A classification was proposed: type I, snare noncutting (53 %); type II, clip misdeployment (31 %); and type III, cap misplacement (16 %). Among endoscopic treatments completed, rescue endoscopic mucosal resection was performed in 57 patients (74 %), allowing en bloc and R0 resection in 71 % and 64 %, respectively. The overall adverse event rate was 27.3 %. Pooled estimates for the rates of failure, complications, and rescue endoscopic therapy were similar for low and high volume centers (P = 0.08, P = 0.70, and P = 0.71, respectively).Conclusions Colorectal EFTR with the FTRD is a challenging technique with a non-negligible rate of technical failure and complications. Experience in rescue resection techniques and multidisciplinary management are mandatory in this setting.